1982
DOI: 10.1073/pnas.79.10.3138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytokeratin antigens in Novikoff ascites hepatoma.

Abstract: Further characterization of three polypeptide antigens present in Novikoff ascites hepatoma (molecular weights 39,000, 49,000, and 56,000-p39 p49, and p56, respectively), has established the identity of these proteins as cytokeratins. Two-dimensional gel electrophoresis revealed that each of the three proteins exists in several isoelectric forms, all characteristic of the keratins. The antigens p39 and p56 had amino acid compositions compatible with this family of proteins, and immunofluorescence microscopy lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…When preparations from PC12 cytoskeletons enriched in IFs were examined by one-(not shown) and two-dimensional gel electrophoresis (Fig. 6, a-c), two major polypeptides of Mr 55,000 and 49,000 were seen which were identical in positions to cytokeratins A and D as originally described in rat hepatocytes (Franke et al, 1981a) and intestinal cells (Franke et al, 1981d) as well as in various rat hepatoma cell cultures (Franke et al, 1981b,c;Schmidt et al, 1982;Venetianer et al, 1983). These two polypeptides, which occur in equimolar amounts in heterotypic tetrameric complexes (Quinlan et al, 1984), are the rat polypeptides equivalent to human cytokeratins Nos.…”
Section: Biochemical Analysesmentioning
confidence: 53%
“…When preparations from PC12 cytoskeletons enriched in IFs were examined by one-(not shown) and two-dimensional gel electrophoresis (Fig. 6, a-c), two major polypeptides of Mr 55,000 and 49,000 were seen which were identical in positions to cytokeratins A and D as originally described in rat hepatocytes (Franke et al, 1981a) and intestinal cells (Franke et al, 1981d) as well as in various rat hepatoma cell cultures (Franke et al, 1981b,c;Schmidt et al, 1982;Venetianer et al, 1983). These two polypeptides, which occur in equimolar amounts in heterotypic tetrameric complexes (Quinlan et al, 1984), are the rat polypeptides equivalent to human cytokeratins Nos.…”
Section: Biochemical Analysesmentioning
confidence: 53%
“…It has been clearly demonstrated that IF of epithelial cells grown in vivo or in culture are biochemically and immunologically related to prekeratin (Franke et al, 1978d;Sun et al, 1979). Based on this fact, antiprekeratin antiserum has been widely used to study the three-dimensional organization of this system of filaments in epithelial cells by immunocytochemical techniques (Franke et al, 1978a,b,c,d;Sun et al, 1979;Franke et al, 1980;Osborn et al, 1980;Asch et al, 1981;Dabike et al, 1981;Eckert and Daley, 1981;Franke et al, 1981a,b;Horwitz et al, 1981;Wu and Rheinwald, 1981;Banks-Schlegel, 1982;Schmidt et al, 1982;Staufenbiel and Deppert, 1982). The biological function of IF and the way they interact with other fibrillar systems is still unclear; however, they have been related to functions such as locomotion of cultured cells, organelle attachment and movement, and determination of the cell shape (Goldman et al, 1979).…”
mentioning
confidence: 99%